2018
DOI: 10.3390/ijms20010096
|View full text |Cite|
|
Sign up to set email alerts
|

Chemokines and Chemokine Receptors: Orchestrating Tumor Metastasization

Abstract: Metastasis still represents the primary cause of cancer morbidity and mortality worldwide. Chemokine signalling contributes to the overall process of cancer growth and metastasis, and their expression in both primary tumors and metastatic lesions correlate with prognosis. Chemokines promote tumor metastasization by directly supporting cancer cell survival and invasion, angiogenesis, and by indirectly shaping the pre-metastatic niches and antitumor immunity. Here, we will focus on the relevant chemokine/chemoki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
104
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(118 citation statements)
references
References 223 publications
(360 reference statements)
0
104
0
2
Order By: Relevance
“…The role of chemokines in angiogenesis has gained increasing levels of attention. Current publications have mainly focused on the function of chemokines in tumor angiogenesis . Several studies have also suggested that chemokines have an important role in vascular remodeling .…”
Section: The Role Of Cxcl16 In Normal Pregnancymentioning
confidence: 99%
See 1 more Smart Citation
“…The role of chemokines in angiogenesis has gained increasing levels of attention. Current publications have mainly focused on the function of chemokines in tumor angiogenesis . Several studies have also suggested that chemokines have an important role in vascular remodeling .…”
Section: The Role Of Cxcl16 In Normal Pregnancymentioning
confidence: 99%
“…Current publications have mainly focused on the function of chemokines in tumor angiogenesis. 80,81 Several studies have also suggested that chemokines have an important role in vascular remodeling. 82,83 The angiogenic factors secreted by EVTs perform an important role in the physiological remodeling of maternal spiral arteries.…”
Section: Effect Of Cxcl16 On Angiogenesismentioning
confidence: 99%
“…23 Another study, examining the same chemokine axis in PC, suggests that the CCL5:CCR5 axis promotes PC progression, with both CCL5 and CCR5 being expressed in PC cell lines and tissues. Adapted from Janeway's Immunobiology, 5 Griffith et al, 15 Marcuzzi et al, 16 and Coniglio. 17 Ab, antibody; CCL, chemokine (C-C motif) ligand; DC, dendritic cell; ILC, innate lymphoid cell; MDSC, myeloid-derived suppressor cell; NK, natural killer; pDC, plasmacytoid dendritic cell; TAM, tumor-associated macrophage; TEM, T-cell effector memory; TFH, T-follicular helper; TFR, T follicular regulatory cell; Th, helper T cell; Treg, regulatory T.…”
Section: T Lymphocytesmentioning
confidence: 99%
“…Chemokine/chemokine receptor axis plays important roles in determining tumor development and metastasis [5][6][7]. Chemokine receptors were expressed on both immune cells and tumor cells, which could recruit immune cells to the tumor microenvironment, as well as driving metastatic process [6,7].…”
Section: Introductionmentioning
confidence: 99%